Anisotropic dependence of radiation from excitons in Ga2O3/MoS2 heterostructure. Issue 47 (24th October 2022) - Deng, Zexiang
Abstract : The anisotropic dependence of radiation arising from exciton recombination in the Ga2 O3 /MoS2 heterostructure is investigated, using density functional theory and the Bethe–Salpeter equation. Abstract : The anisotropic dependence of radiation arising from exciton recombination in the Ga2 O3 /MoS2 heterostructure is investigated, using density functional theory and the Bethe–Salpeter equation. The wurtzite (WZ) and zinc blende (ZB) structures of the Ga2 O3 monolayer with ferroelectric (FE) properties are assembled with a MoS2 monolayer. Projected band structure, charge transfer and life time of excitons are discussed, to analyze which transition may be important to the creation of excitons from the electron–hole pair. A general formula of the angle-dependent intensities of radiation is derived. The characteristics of angle-dependent intensities that are closely related to the dipole moment of excitons are discussed, from the viewpoint of in-plane and out-of-plane polarizations. These predictions on radiation of the Ga2 O3 /MoS2 heterostructure should guide exciton dynamics in low dimensional systems and rational design of optoelectronic devices.